Stem injection of insecticides to control herbivorous insects on Eucalyptus nitens - Gous, S.F.; Richardson, B. (New Zealand Plant Protection, 2008)
To minimise environmental impact in urban and recreational environments insecticides may be injected directly into the vascular system of trees rather than by conventional foliar spray application In previous stem injection trials the majority of injected insecticides did not provide effective control of herbivorous insects This was largely because of the insolubility of the formulated insecticide products available in New Zealand Three water soluble insecticides acephate imidacloprid and emamectin benzoate were injected directly into the xylem of Eucalyptus nitens In subsequent laboratory bioassays the effect of these insecticides were assessed on two leaf feeding insects Uraba lugens (gum leaf skeletoniser) and Trachymela sloanei (a eucalyptus tortoise beetle) The results indicate that acephate may be a suitable candidate for protecting trees using stem injection of insecticides but in this study imidacloprid and emamectin benzoate were not effective